Clown in a cornfield - Cesare, Adam (2020)
"Quinn Maybrook just wants to make it to graduation. She might not make it to morning. When Quinn and her father move to a tiny town with a weird clown for a mascot, they're looking for a fresh start. But ever since the town's only factory shut down, Kettle Springs has been cracked in half. Most of the town believes that the kids are to blame. After all, the juniors and seniors at Kettle Springs High are the ones who threw the party where Arthur Hill's daughter died. They're the ones who set the abandoned factory on fire and who spend all their time posting pranks on YouTube. They have no respect and no idea what it means to work hard. For the kids, it's the other way around. And now Kettle Springs is caught in a constant battle between old and new, tradition and progress. It's a fight that looks like it will destroy the town. Until one homicidal clown with a porkpie hat and a red nose decides to end it for good. Because if your opponents all die, you win the debate by default."--
"Quinn Maybrook and her father have moved to tiny, boring Kettle Springs, to find a fresh start. But what they don't know is that ever since the Baypen Corn Syrup Factory shut down, Kettle Springs has cracked in half. On one side are the adults, who are desperate to make Kettle Springs great again, and on the other are the kids, who want to have fun, make prank videos, and get out of Kettle Springs as quick as they can. Kettle Springs is caught in a battle between old and new, tradition and progress. It's a fight that looks like it will destroy the town. Until Frendo, the Baypen mascot, a creepy clown in a pork-pie hat, goes homicidal and decides that the only way for Kettle Springs to grow back is to cull the rotten crop of kids who live there now. "--Amazon.
Keywords: Fathers and daughters -- Juvenile fiction; City and town life -- Juvenile fiction; Clowns -- Juvenile fiction; Murderers -- Juvenile fiction; Teenagers -- Crimes against -- Juvenile fiction; Conflict of generations -- Juvenile fiction; Young adult fiction; Horror tales; Fathers and daughters -- Fiction; City and town life -- Fiction; Clowns -- Fiction; Murderers -- Fiction; Young adult fiction; City and town life; Clowns; Conflict of generations; Fathers and daughters; Murderers; Teenagers -- Crimes against; Young adult fiction; Young adult works; Fiction; Horror fiction; Horror fiction; Horror fiction